2 TREATMENT OF PEDIATRIC CROHN'S DISEASE PATIENTS WITH EARLY PERIANAL COMPLICATIONS. (18th January 2018) - Adler, Jeremy; Gadepalli, Samir; Zacur, George; Jarboe, Marcus; Dombkowski, Kevin
Abstract: Background: Among pediatric patients with Crohn disease (CD), the variation in treatment of perianal complications (PaC) has not been characterized. The presence of PaC at CD diagnosis predicts more aggressive CD. If introduced early, steroid sparing medical therapy (SSMT) improves outcomes and decreases steroid use. We sought to describe the variation in treatment among pediatric patients with newly diagnosed CD with PaC. Methods: We used the ImproveCareNow Network registry to identify CD patients (2006–2014). We included only consented patients enrolled ≤60 days from CD diagnosis; PaC status by 60 days was classified (present/absent). Clinicians prospectively recorded physical examination, Paris phenotype and medication use. We evaluated time from CD diagnosis to initiation of therapies including immunomodulators (IMM), anti-tumor necrosis factor α (anti-TNFα), dual therapy (IMM + anti-TNFα) and SSMT (IMM or anti-TNFα; Table 1). Associations were evaluated between PaC and therapies (chi-square); time from CD diagnosis to SSMT initiation was analyzed (Cox proportional hazard models). Results: The registry included 6, 624 CD patients from 65 sites; 1, 730 (26%) met inclusion criteria of whom 286 (17%) developed PaC by 60 days. The most common therapies were SSMT (64%), corticosteroids (56%) and IMM (48%, Table 1). By 90 days, those with PaC were more likely to be started on SSMT (71%) vs. those without (57%; p<0.0001), and more likely to be on anti-TNFα (35% vs. 13%; p<0.0001) or dual therapy (10% vs. 4%; p<0.0001). PaC patients were less likely to be on corticosteroids (48% vs. 58%; p=0.001). By 12 months, 21% of those with PaC and 37% of those without PaC had not yet started SSMT (Figure 1; p<0.0001). Conclusion: There is wide variation in treatment of PaC among pediatric patients with CD. Delay in SSMT is common, as is corticosteroid use. Timely introduction of SSMT for treatment of PaC is important to prevent further complications and minimize corticosteroid use.